Resting vagal tone, alpha amylase and cortisol levels in women with eating disorders before and after psychotherapy - Simone Munsch; Nadine Messerli-Bürgy; Marius Rubo; Andrea H. Meyer; Kathrin Schopf; Nadine Humbel; Felicitas Forrer; Dirk Adolph; Jürgen Margraf; Silvia Schneider (PLoS ONE, 2025)
Background Eating disorders such as Anorexia Nervosa (AN) and Bulimia Nervosa (BN) were previously found to partly entail alterations in stress physiology including salivary cortisol (sC), and salivary alpha amylase (sAA) at rest and basal vagal tone (HF-HRV), compared to individuals without mental disorders or with mixed mental disorders (anxiety and depressive disorders), but corresponding data remain scarce and are not entirely consistent. Method HF-HRV, sC and sAA at rest were assessed in a female sample of 58 individuals with AN and 54 individuals with BN before and after psychotherapy and contrasted against measurements from 59 female individuals suffering from mixed disorders and 101female healthy controls. Results Values for sC were elevated in AN compared to all other groups, those for HF-HRV were highest in both AN and BN and lowest in mixed mental disorders and no differences were found at rest for sAA. During psychotherapy, HF-HRV changed more in AN and BN groups than in HC or mixed samples. sC and sAA remained unchanged. There was no association between BMI and stress physiology. Conclusion Alterations in stress physiology present differently across EDs and mixed mental disorders. Correlates of physiological functioning remained mostly stable throughout 3 months of psychotherapy. Only basal vagal tone was normalized in AN/BN in comparison to HC. This might indicate that physiological changes can occur early, but mostly take longer to change during treatment. Trial registration: Data were assessed during a multi-site cross- and longitudinal experimental trial registered at the German Clinical Trials Registry (trial number: DRKS00005709; see [1] for details).